English - have a go : student's book - Nery, Caryn ([South Melbourne, Vic.] : Oxford University Press, 1997)
The series, through the life of the Jones family, presents grammar, pronunciation and useful sentences for learners of English. There is also a segment introducing Australian families, including families from Korean, Italian, Chinese, English, Aboriginal and Greek backgrounds.
Keywords: English language; Foreign speakers; English language; English language -- Problems, exercises, etc; English language -- Sound recordings for foreign speakers